GENDER AND ETHNICITY DIFFERENCES IN TAX COMPLIANCE - Jeyapalan Kasipillai; Hijattulah Abdul Jabbar (Asian Academy of Management Journal, 2006)
The purpose of this study is to investigate whether gender and ethnicity differences occur in relation to tax compliance attitude and behavior. Prior studies on tax compliance have focused little on gender as a predictor of compliance. In Malaysia, ethnic background of a taxpayer could be a major determinant of tax compliance. A personal interview approach is used to obtain information from taxpayers in urban towns. A t-test suggests that males and females were found to have similar compliant attitude. As for ethnicity, a similar result was observed. Results of a regression analysis indicate that gender, academic qualification, and the person preparing tax return were statistically significant as determinants of non-compliant attitude. In terms of compliant behavior, a regression analysis revealed that "attitude towards non-compliance" and "receipt of cash income" were two significant explanatory variables of tax non-compliance behavior of understating income knowingly. The findings of this study are useful for policy implications in identifying groups that require additional attention to increase voluntary tax compliance.